Paying to Program? Engineering Brand and High-Tech Wages - Tambe, Prasanna; Ye, Xuan; Cappelli, Peter (Management Science, 2020)
We test the hypothesis that information technology (IT) workers accept a compensating differential to work with emerging IT systems and that employers that invest in these systems can, in turn, capture greater value from the wages they pay. We show that much of the utility IT workers derive from these systems is from skills acquired on the job. This is principally true for younger workers at employers where skill development is encouraged, and the effects are stronger in thicker markets where workers with newer skills have more outside options. An analysis of the text in online employer reviews supports the notion that IT workers value access to interesting IT systems above most other employer attributes. These findings are important because (1) they provide evidence of how worker preferences can influence corporate IT investment decisions, (2) they shed light on factors influencing IT skill development, and (3) they point to a potentially important explanation for returns from IT investments. This paper was accepted by Chris Forman, information systems.